Masalah Pengembangan SDM Kesehatan di Klinik “X” Palembang - Fatimah, Mustika (JURNAL KESEHATAN TERAPAN, 2022)
Background: health services in a health care place are required to have quality health workers, so that in the end it will form a good impression for the health service place. Methods: This observational descriptive study was conducted in 2020-2021 with a population of health human resources at “X” clinic Palembang with a total sampling technique and data were collected using observation and interview methods as well as documentation studies. Results: Health human resources development activities at “X” clinic Palembang such as seminars were conducted several times by general practitioners, dentists, nurses, and pharmacists to increase competence with independent funds. Activities in the form of workshops are only attended by nurses 3 times per year for the benefit of increasing competence and clinical interests using independent funds and clinic funds, respectively. Training activities are carried out once per year by general practitioners and midwives for clinical purposes using clinical funds and 2 times per year by dentists for competency improvement using independent funds. The development of health human resources in the clinic has not been maximized. Keywords: Clinic, Development, Health Human Resources